Old friends in new constellations: the hematopoetic growth factors G-CSF, GMCSF, and EPO for the treatment of neurological dDiseases - Maurer, Martin H.; Schäbitz, Wolf-Rüdiger; Schneider, Armin (Current medicinal chemistry, 2008)
Currently, growth factors which have been identified in hematopoiesis and angiogenesis are re-considered as therapeutical agents in a number of neurological diseases, mainly neurodegenerative disorders like Parkinsons Disease, amyotrophic lateral sclerosis (ALS), or cerebrovascular events such as stroke. Among these growth factors, erythropoietin (EPO) and granulocyte colony-stimulating growth factor (G-CSF) are the most prominent. With regard to neurological disease, EPO has been tested in clinical trials for potential use in stroke, schizophrenia, and addiction, G-CSF is currently under clinical investigation for stroke treatment. The major advantage of these growth factors is their well-described pharmacological behavior and their clinical use over several years. A number of mechanisms of action in the CNS have been identified that are probably important for the beneficial action of these factors in animal models of disease, the most relevant relating to neuroprotection, neuroplasticity and stem cell growth and differentiation. In this review, we will discuss the current efforts and prerequisites of novel growth factor therapies for neurodegenerative diseases with regard to their possible mechanism of action on the molecular level and their effects on brain-derived stem cell populations. Additionally, we will describe the necessities for future research before such therapies can be envisioned.